Testosterone does not mediate the correlation between dietary inflammation and serum klotho levels among males: insights from NHANES database - Du, Siyu; Zhao, Jieyi; Chou, Xinyue; Peng, Jingyu; Cao, Qi; Zeng, Yimiao; Ao, Lu; Wang, Xiaoyu (Frontiers in Endocrinology, 2024)
Serum Klotho (S-Klotho) is a transmembrane protein holds pivotal roles in antiaging. The Dietary Inflammation Index (DII), a meticulously dietary tool, quantifies the inflammatory potential of an individual's diet. The existing research strongly suggests that a low DII diet plays a significant role in delaying aging and reducing aging-related symptoms in males. Testosterone could potentially act as a mediating intermediary between DII and S-Klotho. However, this aspect remains unexplored. This study aims to investigate the potential causal link of testosterone between DII and S-Klotho in males. We utilized data from National Health and Nutrition Examination Survey (NHANES) which focused on male participants from 2013-2016. Mediation analyses were used to investigate the effects of testosterone (TT), free testosterone (FT), and free androgen index (FAI) on the DII-S-Klotho relationship, using three modes adjusting for covariates. Mediation analysis unveiled a significant inverse correlation between DII and S-Klotho levels